An indicator for ecosystem externalities in fishing: Supporting material - Lars Ravn-Jonsen; Ken H. Andersen; Niels Vestergaard (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2015)
This supporting material for An Indicator for Ecosystem Externalities in Fishing provides the estimations of the cost model parameters, establishes a price model, performs sensitivity analyses of the cost model parameters and analyzes sensitivity with respect to the control variable.
Keywords: 330; Production function; Price model; Sensitivity analyses